GEMPA MENURUT AL QURAN DAN SISTEM STRUKTUR BANGUNAN - Sedayu, Agung (ULUL ALBAB Jurnal Studi Islam, 2010)
Earthquake is very attractive to be studied in perspective of al Quran and also system of building construction. Earthquake as nature phenomenon was told as disaster which mentioned in al Quran, and earthquake is also load for building construction. Earthquake can be caused by formation of earth coat which do not uniform, this matter cause coat try to move in its position. The change of coat was caused formation of earth itself and uncontrolled exploitation of nature resource forcing geology formation become to change. Especial principle of civil building is to human target, and has the meaning that element of essence of human being placed highest on course to be protected against by all kinds of building encumbering. In planning building resistances to earthquake, used a planning concept base on performance (performance based-design) by specifying level several of structure performance (multiple performance levels). This performance grade is level of building performance expected will be done at the building structure accept earthquake load with the certain intensity level. Conception the the planning become the newest trend in this time, where this concept represent the combination from aspect of prisoner and helper aspect. Characteristics of seismic structure are evaluated by using performance evaluation that composed pushover analyzes and inelastic dynamic time history analyze.